Is additional schooling worthless? Revising the zero returns to compulsory schooling in Germany - Kamila Cygan-Rehm (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This study estimates the effect of compulsory schooling on earnings. For identification, I exploit a German reform that extended the duration of secondary schooling in the 1960s. I find that hourly wages increase by 8% per additional year of schooling. This result challenges a study by Pischke and von Wachter (2008) who find zero returns to schooling using the same survey data and reform. I show that their small and insignificant estimates suffer from unconsidered institutional details. A complementary analysis using social security records confirms significant effects on earnings, but yields no effects on employment and eligibility for public transfers.
Keywords: I21; I26; J31; 330